2018
DOI: 10.1002/jbm.b.34076
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of vascular grafts with circumferentially aligned microfibers in a rat abdominal aorta replacement model

Abstract: Long-term results of implants in small animal models can be used to optimize the design of grafts to further promote tissue regeneration. In previous study, we fabricated a poly(ɛ-caprolactone) (PCL) bi-layered vascular graft consisting of an internal layer with circumferentially aligned microfibers and an external layer with random nanofibers. The circumferentially oriented vascular smooth muscle cells (VSMCs) were successfully regenerated after the grafts were implanted in rat abdominal aorta for 3 months. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
4
23
0
Order By: Relevance
“…The complete in vivo degradation of PCL takes approximately 18 months. Slow degradation rates of polymers are considered beneficial in the avoidance of rapid mechanical loss during early remodeling stages of tissue regeneration ( 34 , 45 ). At 7 months after VI of hMPB (hMPB-V7m), the PCL fibers exhibited signs of fragmentation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete in vivo degradation of PCL takes approximately 18 months. Slow degradation rates of polymers are considered beneficial in the avoidance of rapid mechanical loss during early remodeling stages of tissue regeneration ( 34 , 45 ). At 7 months after VI of hMPB (hMPB-V7m), the PCL fibers exhibited signs of fragmentation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S23). Previously, it was shown that ECM deposition effectively compensated for loss of mechanical strength due to polymer degradation, and this helped avoid graft dilatation or rupture ( 45 , 46 ). In support of this, we found no signs of dilatation or rupture in hMPB-V7m ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, their lost physiological function and calcification concluded that geometric resemblance alone is not as effective as was initially believed. [ 92 ] In a concerted effort, immobilization of heparin on topographically aligned luminal surface resulted in superior neovessel remodeling, long‐term patency, and rapid in situ endothelialization in rabbit carotid artery after 3 months. [ 93 ] TEVGs with circumferentially oriented micro‐channels guided cell orientation and assisted rapid endothelialization via recruitment and M2 polarization of macrophages in rat aortic implantation model.…”
Section: Emerging Strategies To Improve the Tevg Performancementioning
confidence: 99%
“…However, the contraction and relaxation function of regenerated neoartery almost disappeared. Other factors of grafts should be considered to achieve the regenerated artery similar to the native vessels after long-term implantation, but this is still a potential orientation in AAA graft ( 94 ). What is more, combining electrospinning and 3D printing to create patient-specific nanofiber tissue-engineered vascular grafts (TEVGs) is a feasible technology as a future clinical option.…”
Section: Nanoparticles In Abdominal Aortic Aneurysm Stent Graftmentioning
confidence: 99%